On Being Positive: Concerns and Counterpoints - Fineman, Stephen (Academy of Management Review, 2006)
In this article I examine the attractions and shortcomings of the “positive” neohumanisitic turn in organizational theorizing and how positivity might be developed. I evaluate positivity's moral and cultural underpinnings and claims to separate positive from negative emotions, and I explore the deployment of positiveness in HRM programs of empowerment, emotional intelligence, and fun at work. I conclude with suggestions on how positive scholarship could be reconfigured in light of the present critique and against the emancipatory ideas of critical organizational theory.